Evaluasi Pemberian Informasi Obat Pada Pasien Tuberkulosis Di Rumah Sakit X Periode April 2025 - Dewantoro, Agung; Haryani, Setianti; Rahajeng, Suny Koswara (PHRASE (Pharmaceutical Science) Journal, 2025)
Drug Information Service (PIO) plays a crucial role in treatment success because accurate and precise information regarding drug use greatly supports the effectiveness of therapy. The objective of this study was to evaluate the provision of drug information to TB patients at Hospital X. Methods: This research used a quantitative descriptive design. Data were collected through a questionnaire distributed to 100 respondents selected using an accidental sampling technique based on predetermined inclusion criteria. Results : Treatment duration 4 months 61 respondents (61%), TB anatomical location pulmonary TB 100 respondents (100%), Treatment phase continuation phase 61 respondents (61%), Most commonly prescribed additional drug group vitamins (45.45%), Most commonly prescribed additional drug type Kurkumax on 40 respondent (40%), The provision of PIO services for TB patients at Hospital X was found to be in good condition (91%). Conclusion: The process of providing anti-tuberculosis drug information at Hospital X is categorized as good.